Adapting Inland Fisheries Management to a Changing Climate. Issue 7 (29th June 2016) - Paukert, Craig P.; Glazer, Bob A.; Hansen, Gretchen J. A.; Irwin, Brian J.; Jacobson, Peter C.; Kershner, Jeffrey L.; Shuter, Brian J.; Whitney, James E.; Lynch, Abigail J.
Abstract : Natural resource decision makers are challenged to adapt management to a changing climate while balancing short‐term management goals with long‐term changes in aquatic systems. Adaptation will require developing resilient ecosystems and resilient management systems. Decision makers already have tools to develop or ensure resilient aquatic systems and fisheries such as managing harvest and riparian zones. Because fisheries management often interacts with multiple stakeholders, adaptation strategies involving fisheries managers and other partners focused on land use, policy, and human systems, coupled with long‐term monitoring, are necessary for resilient systems. We show how agencies and organizations are adapting to a changing climate in Minnesota and Ontario lakes and Montana streams. We also present how the Florida Fish and Wildlife Commission created a management structure to develop adaptation strategies. These examples demonstrate how organizations and agencies can cope with climate change effects on fishes and fisheries through creating resilient management and ecological systems.